ADAT PERKAWINAN KALONDO BUNTI DESA KAMBILO: Studi Kasus Kecamatan Wowo Kabupaten Bima (Moderation: Journal of Islamic Studies Review, 2025)
This research aims to find out how the Kalondo Bunti Tradition in the Marriage of the Bima Community in Kambilo Village, Wawo District according to Islamic Law. In this study, a type of descriptive qualitative research is used with field studies of Anthropological and Sociological approaches. The collection techniques are observation, interviews, and documentation. Meanwhile, the data analysis processing technique uses reduction, data presentation and conclusion drawn. The conclusion of this study states that the practice of traditional marriage of Kalondo Bunti in the Bima community should not be carried out because the mafsadad for the bride-to-be is more than the benefits, unless there is mahram assistance. This can cause unwanted things (slander), so prevention must be done rather than carrying it out.
Keywords: Traditional Weddings; Bima Community; Kalondo Bunti, Islamic Law